Reply to Discussion by M. Pfister on Verification and validation of a computational fluid dynamics (CFD) model for air entrainment at spillway aerators - Aydin, M. Cihan; Ozturk, Mualla (Natl Research Council Canada-N R C Research Press, 2010)
[Abstract Not Available]